STML students’ satisfaction of using MOOCs: study on synchronous and asynchronous videos - Abd Rahim, Nur Ashikin; Mohamad, Mawaddah (Universiti Utara Malaysia, 2020)
Massive Open Online Courses or better known as MOOCs are free and open online learning courses. MOOC is one of the latest platforms that has been introduced and used as one of the latest teaching and learning approaches in the modern technology era. This study was conducted to examine student satisfaction in the use of MOOCs among the School of Technology Management and Logistic (STML) students. There are three objectives in conducting this study, first is to identify the level of students satisfaction of using MOOCs video. Second, is to examine the relationship between the use of synchronous video with students' satisfaction of using MOOCs and third is to analyze the relationship between the use of asynchronous video with students' satisfaction of using MOOCs. A set of questionnaires was used as a data collection medium and was distributed to 100 respondents which are the STML students. Subsequently, the data obtained were then analyzed using SPSS Version 25.0 (Statistical Package for Social Science) and described in descriptive and inference statistics. The findings show that the satisfaction of using MOOCs among the STML students’ is at a satisfactory level. The results show that students are very satisfied with the use of MOOCs in teaching and learning sessions nowadays.